PENATALAKSANAAN GIZI PADA PASIEN DIABETES MELLITUS TIPE 2 DENGAN CHF ET CAUSA HHD DI RSUD BANTEN - Salsabila, Nur; Nuradhiani, Annisa; Ratnasari, Ratnasari (Universitas Sultan Ageng Tirtayasa, 2025)
Diabetes mellitus is a major chronic disease and a serious global health threat, ranking as the 9th leading cause of death worldwide. It results from an imbalance between insulin supply and demand, leading to glucose accumulation in the blood and potential complications. This case study aimed to plan and implement appropriate nutritional care for a patient with diabetes. The study used a descriptive method with a case study approach and was conducted over a period of three days. During the intervention, the patient's food intake gradually increased, although it had not yet reached the targeted level by the third day. A major challenge faced was the patient’s recurring nausea, which often led to incomplete meals. Despite efforts to motivate and encourage the patient to consume the provided meals, this issue persisted until the final day of care. Menu modifications were suggested based on the principles and dietary requirements of diabetes management. However, the patient was reluctant to accept changes in the food format and preferred to stick to familiar food textures and forms.